A fatal outbreak of ST11 carbapenem-resistant hypervirulent Klebsiella pneumoniae in a Chinese hospital: a molecular epidemiological study. Issue 1 (January 2018) - Gu, Danxia; Dong, Ning; Zheng, Zhiwei; Lin, Di; Huang, Man; Wang, Lihua; Chan, Edward Wai-Chi; Shu, Lingbin; Yu, Jiang; Zhang, Rong; Chen, Sheng
Summary: Background: Hypervirulent Klebsiella pneumoniae strains often cause life-threatening community-acquired infections in young and healthy hosts, but are usually sensitive to antibiotics. In this study, we investigated a fatal outbreak of ventilator-associated pneumonia caused by a new emerging hypervirulent K pneumoniae strain. Methods: The outbreak occurred in the integrated intensive care unit of a new branch of the Second Affiliated Hospital of Zhejiang University (Hangzhou, China). We collected 21 carbapenem-resistant K pneumoniae strains from five patients and characterised these strains for their antimicrobial susceptibility, multilocus sequence types, and genetic relatedness using VITEK-2 compact system, multilocus sequence typing, and whole genome sequencing. We selected one representative isolate from each patient to establish the virulence potential using a human neutrophil assay and Galleria mellonella model and to establish the genetic basis of their hypervirulence phenotype. Findings: All five patients had undergone surgery for multiple trauma and subsequently received mechanical ventilation. The patients were aged 53–73 years and were admitted to the intensive care unit between late February and April, 2016. They all had severe pneumonia, carbapenem-resistant K pneumoniae infections, and poor responses to antibiotic treatment and died due to severe lung infection, multiorgan failure, or septic shock. All five representative carbapenem-resistant K pneumoniae strains belonged to the ST11 type, which is the most prevalent carbapenem-resistant K pneumoniae type in China, and originated from the same clone. The strains were positive on the string test, had survival of about 80% after 1 h incubation in human neutrophils, and killed 100% of wax moth larvae ( G mellonella ) inoculated with 1 × 10 6 colony-forming units of the specimens within 24 h, suggesting that they were hypervirulent K pneumoniae . Genomic analyses showed that the emergence of these ST11 carbapenem-resistant hypervirulent K pneumoniae strains was due to the acquisition of a roughly 170 kbp pLVPK-like virulence plasmid by classic ST11 carbapenem-resistant K pneumoniae strains. We also detected these strains in specimens collected in other regions of China. Interpretation: The ST11 carbapenem-resistant hypervirulent K pneumoniae strains pose a substantial threat to human health because they are simultaneously hypervirulent, multidrug resistant, and highly transmissible. Control measures should be implemented to prevent further dissemination of such organisms in the hospital setting and the community. Funding: Chinese National Key Basic Research and Development Program and Collaborative Research Fund of Hong Kong Research Grant Council.